A clinical case of lung damage in granulomatosis with polyangiitis - A. Yu. Kraposhina; I. V. Demko; E. A. Sobko; N. V. Gordeeva; I. A. Soloveva; I. V. Matveeva; O. V. Kazmerchuk; A. B. Katser; Yu. I. Abramov; N. V. Malchik (Бюллетень сибирской медицины, 2021)
The article presents a case of granulomatosis with polyangiitis, which is difficult for clinical diagnosis. Recently, the incidence of systemic vasculitis has increased, and given the similarity of clinical symptoms with other pathologies, a doctor of any specialty should carry out differential diagnosis. Granulomatosis with polyangiitis is characterized mainly by damage to the upper respiratory tract, lungs, and kidneys. The main method for diagnosing granulomatosis with polyangiitis is biopsy with histological examination,  which allows to detect inflammation in the affected tissues. A feature of granulomatosis with polyangiitis is detection of antineutrophil cytoplasmic antibodies in the blood serum. However, these antibodies are recorded only in 80% of patients and are not detected in the remission phase, which makes diagnosis much more difficult.